2017
DOI: 10.1177/0218492317738672
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myofibroblastic lung tumor with dysphagia in a 4-year-old child

Abstract: Inflammatory myofibroblastic tumors of the lung are rare in adults but common among pediatric lung tumors. A 4-year-old girl was evaluated for respiratory symptoms, dysphagia, and weight loss. Radiology revealed a right hilar mass that persisted despite antibiotic treatment. On exploration, a hilar mass involving the pulmonary vasculature, diaphragm and gastroesophageal junction was found. Aggressive surgical excision including a right pneumonectomy was performed. Histopathology confirmed an inflammatory myofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
0
4
2
Order By: Relevance
“…Second, previously published case reports and studies with smaller patient populations described various locations of IMT of the lung that were inconsistent with each other, and also without recognition that the vast majority of pediatric IMT of the lung are pleural-based, as seen in our study. [4][5][6][7]17,18,[21][22][23][24] The pattern of contrast enhancement of pediatric IMT of the lung in our study is also another new finding that is different from the previously published studies. In contrast to the finding of various patterns of contrast enhancement (ie, nonenhancing, homogeneously enhancing, and heterogeneously enhancing) described in previously published studies obtained with a single-detector CT, all IMT of the lung masses showed heterogeneous contrast enhancement in our study with MDCT.…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…Second, previously published case reports and studies with smaller patient populations described various locations of IMT of the lung that were inconsistent with each other, and also without recognition that the vast majority of pediatric IMT of the lung are pleural-based, as seen in our study. [4][5][6][7]17,18,[21][22][23][24] The pattern of contrast enhancement of pediatric IMT of the lung in our study is also another new finding that is different from the previously published studies. In contrast to the finding of various patterns of contrast enhancement (ie, nonenhancing, homogeneously enhancing, and heterogeneously enhancing) described in previously published studies obtained with a single-detector CT, all IMT of the lung masses showed heterogeneous contrast enhancement in our study with MDCT.…”
Section: Discussioncontrasting
confidence: 81%
“…This sets our study apart from many of the previously published studies on pediatric IMT and may explain some of the differences in imaging findings. In addition, the results of our study, which focused on thoracic MDCT findings, with the largest pediatric patient population at the present time, provide new, more specific information on the characteristic MDCT attributes of IMT of the lung in children, many of which differ from the findings of previously published studies obtained with either single-detector CT, mixed pediatric and adult population, or overall smaller patient population size 4–7,17,18,21–24,31,32…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations